Ab initio computational studies of properties and mechanism reaction complex compound between copper (II) and ligan N-phenyl-N'-benzoylthiourea with the Hartree-Fock method - NIAN (NIM 10505018), ARIEL
Structures and properties of thiourea derivative compound N-phenyl-N'-benzoylthiourea have been successfully determined with various kinds of conformational structures which have potential roles as ligands in complex compounds. The most possible structure along with the properties of complex compound between copper (II) and N-phenyl-N'-benzoylthiourea have been performed using Hartree-Fock method with basis set 6-31G. These calculations result in the most stable complex structure through the determination of bond strength of each covalent coordination bond, which is then used to estimate the reaction mechanism for the formation of the complex compound. It was found that the structure of the complex compounds may have two types of coordinate covalent bond, i.e. bonds with sulfur-oxygen atoms and bonds with two N atoms in the ligand. Coordinate covalent bond between central atom with sulfur and oxygen in the ligand is more stable than the one between the central atom with two ligand's nitrogen atoms. The higher energy of the complex between central atom and two nitrogen atoms is due to steric hindrance in the molecule. However, electron transfer from ligand to the central atom of copper (II) that occurs in the formation of coordinate covalent bond is higher in the complex with nitrogen atoms compare to the one with sulfur and oxygen atoms. From the study of reaction mechanism, in can be predicted that the formation of coordinate covalent bonds through the sulfur and oxygen atoms undergo dehydrogenation step on the ligand before the formation of bonds with the central atom.